Credit financing for local development: The subnational debt in the Philippines - Ni\~no Raymond B. Alvina (Asian Development Bank Institute (ADBI), 2019)
Local government units (LGUs) in the Philippines are authorized to borrow or incur debts to finance development, but with certain limitations provided by the Local Government Code of 1991. The main controlling statutory requirement is for provinces, cities, municipalities, and villages not to exceed 20% of their annual regular income going into debt servicing. The range of purposes for which local governments are allowed to borrow are tied up with their expenditure responsibilities, and this varies according to the type and level of LGU, and their capacity to access financing. These commonly include capital investment projects, socioeconomic enterprises, and self-liquidating and income-generating projects. This paper describes the experiences of the Philippines after close to three decades of fiscal decentralization in the country, presents trends and patterns of local debt management practices, highlights the roles of national government agencies and regulatory policies, and proposes emerging ideas and recommendations on how to improve debt management as an important pillar in local finance and decentralization.
Keywords: H75; F34; H81; 330; local government; debt; credit financing; Philippines